Theoretical and experimental investigation of low-volgage and low-loss 25-Gbps Si photonic crystal slow light Mach–Zehnder modulators with interleaved p/n junction - Terada, Yosuke; Ito, Hiroyuki; Nguyen, Hong C.; Baba, Toshihiko (Frontiers in Physics, 2014)
In this study, we investigated the performance of Si lattice-shifted photonic crystal waveguide (LSPCW) Mach–Zehnder modulators theoretically and experimentally. The LSPCW increases the phase shift in modulator to 2.3–2.5 times higher, which allows for size reduction and high performance. On-chip passive loss was reduced to less than 5 dB by optimizing each component. We obtained 25 Gbps clear open eye and 3 dB extinction ratio at a drive voltage of 1.5–1.75 V for 200 μm phase shifter with linear p/n junction when we added a modulation loss of 7 dB. This modulation loss was reduced to 0.8 dB, maintaining other performance, by employing interleaved p/n junction and optimizing doping concentrations.